Systematic review of oral ulceration with bone sequestration. Issue 3 (March 2016) - Palla, Benjamin; Burian, Egon; Klecker, John Richard; Fliefel, Riham; Otto, Sven
Abstract: Background: This article represents the first systematic review entirely dedicated toward a disease called oral ulceration with bone sequestration (OUBS). We performed this review in order to further define and outline this disease. A secondary interest was to recognize the prevalence and importance of OUBS in relation to other oral disorders accompanied by ulceration and bone exposure. Material and methods: The systematic review was registered with PROSPERO (registration number CRD42015024294) and performed in cooperation with Harvard's Countway Library. Searches were built using MeSH terms and proximity operators previously mentioned in OUBS descriptions. Database searches were performed through EMBASE, Medline, and PubMed, followed by a handsearch of bibliographies for relevant articles. Articles were assessed against eligibility and inclusion criteria centering on bone exposure without known etiologic cause. We sought to gather information on patient age, sex, anatomical location, clinical presentation, and comorbidities. PRISMA guidelines were followed. Results: The searches identified 766 records total. Despite considerable inspection, we found only 8 articles qualifying for our review. In the 8 articles, there were a total of 24 patients fulfilling the criteria of OUBS. Although some abstracts mentioned idiopathic nature, most authors presented clinical cases with probable causes to ulceration and sequestration. The mean age of these patients was 43.21 ± 11.94 years. The male to female ratio was 3:1. The predominant area of occurrence was the mandible (n = 23, 95.8%). Conclusion: The representation of OUBS in the literature remains scarce. More data must be generated and gathered on the concept of OUBS so as to determine the true incidence and importance of this disease. Despite rare occurrences of conditions characterizing OUBS, the recent discussion of this topic in the scientific community calls for more knowledge to be brought forth, with great benefit to patients suffering from ulcerative diseases and osteonecrosis.